Persistence of HBsAg‐specific antibodies and immune memory two to three decades after hepatitis B vaccination in adults. Issue 9 (2nd June 2019) - Van Damme, Pierre; Dionne, Marc; Leroux‐Roels, Geert; Van Der Meeren, Olivier; Di Paolo, Emmanuel; Salaun, Bruno; Surya Kiran, Pemmaraju; Folschweiller, Nicolas
Abstract: The duration of protection after hepatitis B vaccination is not exactly known. This phase IV study evaluated antibody persistence and immune memory 20‐30 years after adult immunization with recombinant hepatitis B vaccine (HBsAg vaccine, Engerix‐B ) in routine clinical practice. Men and women 40‐60 years old, with documented evidence of vaccination with three or four HBsAg vaccine doses 20‐30 years earlier and without subsequent booster, were enrolled and received HBsAg vaccine as challenge dose. HBsAg‐specific antibodies (anti‐HBs) and frequencies of HBsAg‐specific circulating memory B cells and CD4 + T cells expressing combinations of activation markers (CD40L, IL2, IFNγ, TNFα) were measured prechallenge, 7 and 30 days postchallenge. Of 101 participants in the according‐to‐protocol cohort for immunogenicity, 90.1% had anti‐HBs concentrations ≥ 10 mIU/mL prechallenge administration; 84.2% and 100% mounted an anamnestic response 7 and 30 days postchallenge, respectively. HBsAg‐specific memory B and CD4 + T cells expressing at least two activation markers were low prechallenge and increased markedly postchallenge. These results suggest sustained immune memory and long‐term protection 20‐30 years after a complete primary HBsAg vaccination course during adulthood, in line with current recommendations that a booster is not needed in fully vaccinated immunocompetent adults.